Planning and Scheduling of a Suspension Cable Bridge Using Project Management Tool Primavera P6 - Jain, Ankit; Punjabi, K. K. (International Journal of Scientific Research in Civil Engineering, 2020)
Attributable to an augmenting context of environment, Construction industry is ever upfront for the development and advancement in tools and equipment features, tools of communication, techniques of efficient management, educating the human resources about it. This unique specialization necessitates highly focused whose construction was planned to start at Bhopal, Madhya Pradesh, India. Project Planning and Controlling tools or techniques. In the current study, implementation of the computer based Project Management software/tool Primavera P6 for the Planning, Scheduling and Allocation of resources for a Suspension Cable Arch Bridge It helps to know the resemblance between the planned the planned progress of construction work and actual progress of the performed work. Thus the essentiality and the advantages of using Primavera will be outlined through the data results obtained. The acceptance of the software Primavera as a platform of scheduling is been on a boom in Multi National Construction Companies, but due to ignorance and lack of Project Management concepts and discourage towards the use of computer based programs, small and medium scale Indian construction companies confront various issues such as inefficient planning, project delays, inefficiency of resources and many other issues. Therefore, attempt to educate one such medium scale construction company about the advantages of Primavera in execution of any construction projects efficiently.